Música na escola: um estudo a partir da psicogenética walloniana - Sugahara, Leila Yuri (2008)
This project had as an objective to study the role of music at school, from the conception teachers and pedagogic coordinators have of music in the total development of the child. As development presupposes learning and the school is the privileged place of this process, being the teacher the mediatory agent and the pedagogic coordinator having as duty teachers formation, it is by teachers and pedagogic coordinators speech that this project intends to discuss the proposed theme. As we understood the teacher s reflection about music in the child s development, in continuous formation programmes, a way to the effectiveness of musical practice at school, we chose to interview teachers who had participated in a continuous formation programme in an urban community in São Paulo country-side. To obtain a broad spectrum of the data collected for the survey, we interviewed: a kinder-garten and nursery school teacher, a multi-disciplinary elementary and junior high school teacher, a Physical Education teacher, an Art teacher, a kindergarten and nursery pedagogic coordinator and an elementary and junior high school coordinator. Henry Wallon s psychogenetics theory guided the data collection and analysis of information. The analysis was carried out from 3 pivotal angles: the constitution of the teacher and the pedagogic coordinator as people, the music in the total development of the child and the music at school. The interviewed people noticed from their daily school practice, that music induces movement, it develops the sense of rhythm, the coordinated motor activity, the memory and it promotes an interaction among people favouring socialization. The continuous music formation courses make it possible for the student to have a better improvement of the musical language potential, in order to improve his development as a complete, entire person in all of his dimensions: affective, cognitive and motor